Short-term Prophylaxis for Delivery in Pregnant Women with Hereditary Angioedema with Normal C1-Inhibitor - Caroline Guth de Freitas Batista de Moraes; Liya Regina Mikami; Lilian Pereira Ferrari; João Bosco Pesquero; Herberto José Chong-Neto; Nelson Augusto Rosario Filho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To verify the efficacy of short-term prophylaxis for vaginal or cesarean section childbirth with plasma-derived C1-inhibitor concentrate in pregnant women. They should have hereditary angioedema (HAE) and normal plasma C1-inhibitor. Methods Case report of pregnant women diagnosed with HAE with normal C1- inhibitor who had been treated with intravenous C1-inhibitor concentrate for prophylaxis of angioedema attacks when hospitalized for delivery. The exon 9 of the Factor 12 (F12) genotyping gene was performed by automatic sequencing in all patients. Results Three cases of pregnant women with HAE with normal serum level of C1- inhibitor are reported. The genetic test detected the presence of a pathogenic mutation in the F12 gene. Deliveries occurred uneventfully and patients had no HAE symptoms in the following 72 hours. Conclusion C1-inhibitor concentrate could be useful to prevent angioedema attacks during and after delivery.